2008
DOI: 10.1002/mrc.2325
|View full text |Cite
|
Sign up to set email alerts
|

Covalent bonding of azoles to quaternary protoberberine alkaloids

Abstract: Adducts of the quaternary protoberberine alkaloids (QPA) berberine, palmatine, and coptisine were prepared with nucleophiles derived from pyrrole, pyrazole, imidazole, and 1,2,4-triazole. The products, 8-substituted 7,8-dihydroprotoberberines, were identified by mass spectrometry and 1D and 2D NMR spectroscopy, including (1)H--(15)N shift correlations at natural abundance. In addition, two adducts of QPA with chloroform and methanethiolate were characterized by using NMR data. Single-crystal X-ray structures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Some modifications of Ber have been carried out trying to improve its bioactivity and bioavailability in antimicrobial, antidiabetic, antihyperlipidemic, and antitumor effects. Modification at C8 and C13 greatly increased the antimicrobial activity of Ber , which is closely related to the substituent chain length. Most of the Ber derivatives with halogen and heteroaromatics on C8 and C9 positions displayed stronger hypoglycemic ability than Ber . , Structure–activity studies on the antitumor effect of Ber mainly focused on the C8, C9, and C13 positions; for example, 13-alkyl derivatives of Ber showed higher antitumor activities than Ber , and a moderate alkyl chain length was beneficial for its antitumor activity. However, almost all these modifications are randomly made and effect-oriented, lacking a structural basis for the mechanism of Ber ’s effects. Most of these derivatives, by inserting either a long aliphatic chain or a heterocyclic ring, may have significant effects but lose the biosafety of Ber because the structures were changed too much.…”
Section: Introductionmentioning
confidence: 99%
“…Some modifications of Ber have been carried out trying to improve its bioactivity and bioavailability in antimicrobial, antidiabetic, antihyperlipidemic, and antitumor effects. Modification at C8 and C13 greatly increased the antimicrobial activity of Ber , which is closely related to the substituent chain length. Most of the Ber derivatives with halogen and heteroaromatics on C8 and C9 positions displayed stronger hypoglycemic ability than Ber . , Structure–activity studies on the antitumor effect of Ber mainly focused on the C8, C9, and C13 positions; for example, 13-alkyl derivatives of Ber showed higher antitumor activities than Ber , and a moderate alkyl chain length was beneficial for its antitumor activity. However, almost all these modifications are randomly made and effect-oriented, lacking a structural basis for the mechanism of Ber ’s effects. Most of these derivatives, by inserting either a long aliphatic chain or a heterocyclic ring, may have significant effects but lose the biosafety of Ber because the structures were changed too much.…”
Section: Introductionmentioning
confidence: 99%
“…IR spectra exhibited vibrations in the range 1653-1664 cm 1 that corresponded to the vibrational frequency of a tertiary amide. PMR and 13 C NMR spectra showed resonances for the berberine molecule that were similar to those of berberine chloride and indicated that this fragment was unchanged [11]. PMR spectra of 2 exhibited resonances for methylene protons of OCH 2 CON as singlet with chemical shifts G 4.99-5.26 ppm.…”
mentioning
confidence: 87%
“…A restricted rotation around the newly formed C-N bond was studied experimentally by temperature-dependent NMR measurements. [19][20][21][22] In addition, the experimental NMR observations were complemented by the molecular modeling and quantum chemical calculations using density functional theory. This paper is arranged as follows: In preparation and characterization section, synthesis of 6-substituted azoles of dihydrobenzo[c]phenanthridine and their characterization by using 1 H and 13 C NMR spectroscopy is described.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetized 5,6‐dihydrobenzo[ c ]phenanthridines were investigated by NMR spectroscopy and computational chemistry with the aim to determine their molecular structures. A restricted rotation around the newly formed C–N bond was studied experimentally by temperature‐dependent NMR measurements . In addition, the experimental NMR observations were complemented by the molecular modeling and quantum chemical calculations using density functional theory.…”
Section: Introductionmentioning
confidence: 99%